Interpersonal rejection as a special type of relationship in the ontological constant 'Me and the Other' - Elena V. Ryaguzova (Saratov State University, 2023)
The article is devoted to interpersonal rejection that is caused by breaking off the relations in the dyad 'Me and the Other'. The scientific interest is focused purely on ostracism. It is associated with ignoring and excluding a group representative from the general communicative and role-based team network as a retaliatory measure or group punishment. The study proposes the triangle of interpersonal rejection subjects. This triangle includes the one who rejects, the one who is rejected, and the one who witnesses the ostracism episode. In accordance with this idea, the author considers the stage theory of ostracism by K. Williams. The theory focuses on the frustration of the needs of a person who has been ostracized and possible consequences of the rejection. The study also presents a universal model by L. Richman and M. Leary, which is based on the development of various motivational tracks depending on the subjective interpretation of a negative interpersonal episode. The model explains the immediate and long-term consequences of this negative experience. Further on, the study provides the analysis of the Responsive Theory of Social Exclusion by G. Freedman, K. D. Williams, J. S. Beer, which focuses on the interactive nature of social exclusion and involves the study of both interacting parties: of those who exclude and of those who are excluded. The paper describes the theory of S. Rudert and R. Greifeneder, which is focused on the third side of the rejection episode, i.e. on the observer, whose action or inaction determines the consequences of interpersonal rejection. The applied aspect of the problem under study consists in the possibility to use the results of theoretical reflection in the educational process. Moreover, it can help to develop preventive measures in order to avert antisocial behavior and to develop psychotherapeutic intervention programs and psychological support programs for the subjects of the rejection.